Exploring the Potential of Transient Receptor Potential: Troubleshooting Troublesome Calcium Thoroughfares in Biomedicine - Ammad Ahmad Farooqi; Abuzar Kaleem; Muhammad Khalid Javeed; Qaisar Mansoor; Shahzad Bhatti (International Journal Bioautomation, 2010)
Transient Receptor Potential-Canonical (TRPC) channels are the border guards residing in the supra-molecular assembly of plasma membrane. TRPCs represent a family of channels that have dual functions of store-operated and second messenger-operated channels in a diversity of cell types. Any disruption in the spatio-temporal organization drastically influences the calcium homeostasis. This review summarizes current interpretations on the infrastructure and characteristic divalent ions regulation in molecular anomalies. A specific targeting of these channels will enable us to get a step closer to personalized medicines.